2021
DOI: 10.1016/j.antiviral.2021.105177
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the molecular mechanism of resistance to vapendavir across a panel of picornavirus species

Abstract: Vapendavir is a rhino/enterovirus inhibitor that targets a hydrophobic pocket in the viral capsid preventing the virus from entering the cell. We set out to study and compare the molecular mechanisms of resistance to vapendavir among clinically relevant Picornavirus species. To this end in vitro resistance selection of drug-resistant isolates was applied in rhinovirus 2 and 14, enterovirus-D68 and Poliovirus 1 Sabin. Mutations in the drug-binding pocket in VP1 (C19… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…4c; Hadfield et al, 1995Hadfield et al, , 1999Smith et al, 1986;Filman et al, 1989;Plevka et al, 2013). The WIN compound vapendavir has been tested in Phase IIb clinical trials for antirhinovirus activity and indeed showed a reduction of viral load; development is ongoing (Lanko et al, 2021). Zika virus is a positive-strand RNA virus.…”
Section: Lipids and Fatty Acids Are Generic Regulators Of Viral Infec...mentioning
confidence: 99%
“…4c; Hadfield et al, 1995Hadfield et al, , 1999Smith et al, 1986;Filman et al, 1989;Plevka et al, 2013). The WIN compound vapendavir has been tested in Phase IIb clinical trials for antirhinovirus activity and indeed showed a reduction of viral load; development is ongoing (Lanko et al, 2021). Zika virus is a positive-strand RNA virus.…”
Section: Lipids and Fatty Acids Are Generic Regulators Of Viral Infec...mentioning
confidence: 99%
“…Development of antivirals against RV infections has been the aim of numerous studies (summarized in multiple recent reviews [72][73][74][75][76][77]). Amongst early antiviral strategies, virustargeting capsid-binding drugs (Pleconaril, Pirodavir, Vapendavir) showed efficacy on preventing virus entry [78,79], but posed issues of rapidly emerging drug resistance [80][81][82]. Other viral targets include conserved regions in the viral RNA-dependent RNA polymerase and viral proteases (rupintrivir), but no drug has achieved approval for clinical use [83,84].…”
Section: Rv Treatment Strategiesmentioning
confidence: 99%
“…Hence, it could slightly suppress EV-A71 RNA replication and protein synthesis, which insufficiently affects virion production. Pocapavir is an enterovirus-specific capsid inhibitor [ 33 ]. It has been used as an investigational drug for the treatment of severe neonatal enteroviral sepsis due to coxsackievirus B3 [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Pocapavir has been reported for clearance of vaccine-derived type 3 poliovirus infection in an infant with underlying X-linked agammaglobulinemia [ 44 ]. The binding site of Pocapavir is within the pocket located in the structural protein VP1, namely canyon [ 33 ]. The Pocapavir binding results in an increase in the stability of the viral capsid, thus preventing conformational changes necessary for receptor interaction and uncoating.…”
Section: Discussionmentioning
confidence: 99%